La insatisfacción con la democracia en el México actual. - Prud’homme, Jean François (El Colegio de México A.C., 2015)
Towards the end of the President Calderón administration, several opinion polls revealed the low level of satisfaction with democracy in Mexico. The aim of this paper is to explain this “mood” that still prevails in Mexican public opinion twelve years after the first democratic change of ruling party in power. The principal argument concerns the weakness of the Mexican democratic state when measured in terms of macroeconomic management and control of violence. It also takes into consideration the efficacy of the political system, the character of pluralism, social inequality and political culture. The conclusions advance arguments in favor of a state that is democratic in both its form and informal aspects.